Energy and economic analysis of motor systems of a ferromagnetic materials processing company, in Itabira-MG (Research, Society and Development, 2022)
This study evaluates the possibilities of changing less efficient drive systems for more efficient ones, through an energy efficiency project for a ferromagnetic material processing company, located in the municipality of Itabira - MG. The article shows the influence of several variables on the operation of the power plant, analyzing a large part of the company's production process and proposing the replacement of part of the company's old machinery by more modern and more efficient machinery, leading to significant savings in the consumption of energy as well as good economic attractiveness.